2012
DOI: 10.1038/nrg3271
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic stability of human pluripotent stem cells

Abstract: Studies using high-resolution genome-wide approaches have recently reported that genomic and epigenomic alterations frequently accumulate in human pluripotent cells. Detailed characterization of these changes is crucial for understanding the impact of these alterations on self-renewal and proliferation, and particularly on the developmental and malignant potential of the cells. Such knowledge is required for the optimized and safe use of pluripotent cells for therapeutic purposes, such as regenerative cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
168
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(170 citation statements)
references
References 108 publications
0
168
1
1
Order By: Relevance
“…More recently, the group of Abyzov et al 6 made use of the clonal nature of humaninduced pluripotent stem cells (hiPSCs) to show that human skin fibroblasts are highly mosaic, with up to 30% of cells carrying copy number variants (CNVs). In the field of human pluripotent stem cell research, a large number of studies have shown that human embryonic stem cell (hESC) cultures are frequently taken over by chromosomally abnormal cells 7,8 , most probably because of a selective advantage caused by the chromosomal aberration 9,10 . Conversely, not much is known on how frequently hESC spontaneously mutate, either through abnormal chromosome segregation or by acquiring small amplifications or deletions, nor on the nature of these changes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the group of Abyzov et al 6 made use of the clonal nature of humaninduced pluripotent stem cells (hiPSCs) to show that human skin fibroblasts are highly mosaic, with up to 30% of cells carrying copy number variants (CNVs). In the field of human pluripotent stem cell research, a large number of studies have shown that human embryonic stem cell (hESC) cultures are frequently taken over by chromosomally abnormal cells 7,8 , most probably because of a selective advantage caused by the chromosomal aberration 9,10 . Conversely, not much is known on how frequently hESC spontaneously mutate, either through abnormal chromosome segregation or by acquiring small amplifications or deletions, nor on the nature of these changes.…”
mentioning
confidence: 99%
“…In recent years, many groups have performed high-resolution screening of somatic cell populations 1,6,11,12 as well as hiPSC and hESC 7,8 and have reported de novo CNVs ranging from 10 kb to several Mb. It is important to bear in mind that these studies are based on the analysis of DNA from extractions from large numbers of cells, which only allows detection of CNVs if they are present in at least 5-10% of the cells 11,12 .…”
mentioning
confidence: 99%
“…This will probably be achieved given time and effort, but many of the non-physiologic conditions taken over from traditional cell culture techniques contribute to the problems. Originally hPSC cultures were thought to be genetically stable, but we have lately learnt about their limitations in this respect (Mitalipova et al, 2005;Lund et al, 2012;Steinemann et al, 2013). Other limitations are costs of culture and complex differentiation protocols, which may require months of labor, media, and supplements.…”
Section: The Genesis Of Gccp 10mentioning
confidence: 99%
“…This is probably only a matter of time, but many of the non-physiological conditions from traditional cell cultures contribute here. Stem cells have been praised for their genetic stability, which appears to be better than for other cell lines, but we have increasingly discovered their limitations in that respect, too (Mitalipova et al, 2005;Lund et al, 2012;Steinemann et al, 2013). The limitations experienced first are costs of culture and slow growth -many protocols require months, and labour, media, and supplement costs add up.…”
mentioning
confidence: 99%